Optimization of alginate alkaline extraction technology from Sargassum polycystum and its antioxidant properties. (March 2018) - Yudiati, E; Santosa, G W; Tontowi, M R; Sedjati, S; Supriyantini, E; Khakimah, M
Abstract: The quality of alginate may differ considerably depending on several aspects. The aims of this research were to identify, characterize the alginate, examine the quality and determine the antioxidant properties. Identification was done phenotypically. Characterization was done by FT-IR spectroscopy by comparing the samples to standard alginate (Sigma, USA). The extraction was done in two treatments: soaked with 5 % NaOCl, extraction of Na2 CO3 (3.0; 5.0; 7.0 and 9.0 %)/EDTA, KCl and precipitated with ethanol (T1) and dried. T2 was pretreated with KOH, HCl, boiled by Na2 CO3 (3.0; 5.0; 7.0 and 9.0 %), depigmented, HCl and NaOH addition precipitated with ethanol absolute and then sundried. Antioxidant properties test were done by DPPH and NBT radical scavenging assays. Phenotypic identification showed that the species was Sargassum polycystum. There were similarities in signal vibration between the samples and the standard. The highest yield was produced from 7.0 % Na2 CO3, while the average yield of T1 (37.56 %) was significantly higher (P ≤ 0.05) than T2 (21.77 %). The level of dynamic viscosity was correlated with alkali concentration. Indication in T1 results showed that the higher alkali concentration, the better yield. The best yield was the lowest viscosity, produced the strongest antioxidant activity.